A Constrained Particle Swarm Optimization Algorithm with Oracle Penalty Method - Dong, Ming Gang; Cheng, Xiao Hui; Niu, Qin Zhou (Applied Mechanics and Materials, 2013)
To solve constrained optimization problems, an Oracle penalty method-based comprehensive learning particle swarm optimization (OBCLPSO) algorithm was proposed. First, original Oracle penalty was modified. Secondly, the modified Oracle penalty method was combine with comprehensive learning particle swarm optimization algorithm. Finally, experimental results and comparisons were given to demonstrate the optimization performances of OBCLPSO. The results show that the proposed algorithm is a very competitive approach for constrained optimization problems.